Transportation aspects of Southern African universities. Volume2 - Wall, Kevin Charles (School of Architecture, Planning and Geomatics, 2024)
Supplementary volume to Thesis by K.C.Wall "Transportation Aspects of Southern African Universities", to Deportment of Urban and Regional Planning, University of Cape Town. October 1971.